APPLICATION OF OPTIMAL CONTROL STRATEGIES FOR PHYSIOLOGICAL MODEL OF TYPE 1 DIABETES - T1D. (2020) - FERJOUCHIA, HANANE; IFTAHY, FATIMA ZAHRA; CHADLI, ASMA; AZIZ, SIHAM EL; KOUIDERE, ABDELFATAH; LABZAI, ABDERRAHIM; BALATIF, OMAR; RACHIK, MOSTAFA
No abstract available